Optimization using Mahalanobis-Taguchi System for inductor component - Mohd Yazid, Abu; F.L.M., Safeiee (IOP Publishing, 2020)
The fourth industrial revolution (IR 4.0) is built upon the digital revolution where technology and people are connected. It does not just present modern techniques for supporting aspects within industry but cover as well the sustainability. Thus, it is very important for electric and electronic (E&E) industry to develop a new technique for a better quality evaluation of product. The aim of this work is to apply Mahalanobis-Taguchi System (MTS) in production environment at E&E industry for a better quality evaluation. MTS is used to classify normal and abnormal observations and optimize various parameters in workstation to produce a better quality product. This work found that positive gain through signal to ratio (SNR) indicated the quality of system still in good condition from February with 0.1244 until December with 0.4432 after insignificant variable have been removed. This work also suggested condition of core should be removed since the variable does not contribute to the system along 2018. Meanwhile, some variables are showed inconsistency of significant to the system such as wire condition, epoxy condition, lead part condition and soldering condition. This concluded that MTS is a practical method for classification and optimization in the industry.